Student Development Challenges and Opportunities in the Digital Era - Hemalia Putri, Della; Puspita, Bunga (International Journal of Students Education, 2024)
The rapid development of digital technology has had a significant impact on the education sector. This development not only provides challenges but also great opportunities for education in the digital era. This article discusses the challenges and opportunities of education in the digital era. Education in the digital era is an era where digital technology has become an integral part of the learning process. Digital technologies such as computers, the internet, and mobile devices have changed the way we learn, teach, and interact in the classroom. The development of digital technology has provided many opportunities and challenges for education in the digital era. Today's students face various challenges such as dependence on technology, easily accessible information, and lack of adequate digital skills but despite these challenges, the digital era also offers unlimited growth opportunities, access to various educational resources, and prepares students facing an increasingly digital future.